IDENTIFIKASI JENIS KELAMIN SIPUT GONGGONG Strombus sp. SECARA MORFOLOGI DI PERAIRAN MADUNG, TANJUNGPINANG, INDONESIA - Susiana; Azwin Apriandi; Rochmady (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Morphological identification as an alternative sex identification of dog conch without damaging the shell and viscera. The study aimed to identify the gender of the dog conch Strombus sp. by morphology. Samples were obtained from fishermen collecting dog conch on the coast of Madung, Tanjungpinang, Indonesia. Samples were collected by hand at low tide. To distinguish between male and female dog conch is done by looking at the shell structure morphologically without seeing the internal organs of the body shell. To see the gonads or reproductive organs is done by removing the whole dog conch by breaking the shell. The shell length was measured using by caliper a precision 0.01 mm. The length of the shell is the distance from the anterior edge to the posterior end of the shell. To know the sex ratio of dog conch type analyzed chi-square. The data obtained were analyzed descriptively. The results showed that of the total sample of 1124 individuals, obtained two types of dog conch are Strombus canarium and Strombus sp. The determination of the gender of morphological dog conch can be seen from the structure of the shell (width and slim). The wide shell shape signifies a female, a slim form of shell signifying a male. The sex ratio of dog conch type S. canarium and Strombus sp. males and females in different ratios.